Medical student career choice’s determinants in Asia: a systematic review - Rizma Adlia Syakurah; Rosyila Rosyila (Intelektual Pustaka Media Utama, 2020)
Asian countries have distinctive cultural patterns and norms that influence one’s decision making process throughout their life, including career choice. This review was intended to explore factors influencing medical students’ career choice in Asia. This review was compiled based on guidelines from PRISMA (Preferred Reporting Items for systematic reviews and Meta-Analysis). Data was searched and collected from studies published from electronic databases such as Pubmed, Europe PMC, Cochrane Databases, Science Direct, BMC Medical Education, ACM, Wiley Online Library and Mendeley with the keyword